DETERMINING INFLUENCE OF UNIVERSITY’S ORGANIZATIONAL CULTURE ON THE HIGHER EDUCATION QUALITY - KHOLIAVKO, Nataliia; OSTROVSKA, Natalia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article describes the conceptual principles of forming the organizational culture of a higher education institution. The conducted research showed the existence of a correlation between the organizational culture of the higher education institution and the quality of its educational services. The concept of organizational culture is interpreted as a set of common values, norms, principles, rules, traditions that unite university employees and its students into a single integrated system, affecting their behavior both in the educational institution and outside of it. There is no universal model of the organizational culture of a higher education institution; specificity of activity, management style, approach to communication with stakeholders etc. - all this causes differences in organizational cultures of different universities. The process of formation of organizational culture is long and dynamic; it is influenced by a complex of exogenous and endogenous factors. The organizational culture allows the participants of the educational process to gain a sense of identity and belonging to a system; it strengthens the trust and deepens the interaction between teachers and students; it develops the set of incentives for innovation, creativity, entrepreneurship and constant improvement of the quality of educational services. The author emphasizes that the organizational culture of a higher education institution motivates teachers and students to take responsibility for the results of their activities, to improve the quality of teaching and learning. The increase in the quality of educational services has a positive effect on the competitiveness of university graduates in the labor market, on the level of satisfaction of employers' requests for qualified and competent personnel, as well as on the innovative activity of business and the pace of innovative development of the national economy.
Keywords: organizational culture; values; norms; higher education institution; university; quality of educational services; students; teachers